Home care program for high-risk pregnancies: a qualitative study of care providers perspectives from Iran - Masoumeh sayahi; Shahrbanoo Salehin; Mehrnoosh Zakerkish; Afsaneh Keramat; Shahrbanoo Goli (BMC Pregnancy and Childbirth)
Abstract Background High-risk pregnancies are accompanied by significant complications for the mother, fetus, and baby if not controlled and received timely care. During home antenatal care, high-risk pregnant women can receive non-medical interventions by a home visitor. Objective This study’s main aim was to explore care providers’ perspectives regarding the home care program for high-risk pregnancies. Materials and methods This qualitative study was conducted in a university hospital and 5 comprehensive health centers in Ahvaz (Iran) from February 2023 to July 2023. The sampling method used was purposive sampling considering the maximum possible diversity, which continued until data saturation. There were 13 in-depth and semi-structured interviews with care providers. Data were simultaneously analysed using Graneheim and Lundman content analysis by MAXQDA version 20 software. Results Data analysis led to the extraction of 3 main categories, 10 subcategories, and 24 main codes. The main categories and subcategories were “support dimension (family and community support for high-risk pregnant women),” “education dimension (empowerment of high-risk pregnant women and care providers),” and “infrastructures of the program (acculturalization, provision of program budget and care tariff, means and equipment, security and ethical issues, manpower, and the necessary arrangements for the home care).” Conclusions Providing home care services for high-risk pregnant women plays a vital role in expanding health justice and ensuring maximum access for high-risk pregnant women to perinatal care. Implementing the home care program requires family and community support, educational empowerment of care providers, and the provision of the necessary infrastructure for the program for high-risk pregnant mothers and their families.